2016
DOI: 10.1515/revecp-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

GDP growth and convergence determinants in the European Union: a crisp-set analysis

Abstract: Economic growth and convergence remains a topical issue. This study uses a crisp-set qualitative comparative analysis of data from European Union countries in order to establish which conditions could be considered necessary and sufficient to make these countries converge. Based on six different conditions (GDP, secondary education, life expectancy, fertility rate, government consumption and inflation rate), this study finds that the main conditions affecting convergence are government consumption ratio (lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Introduced in the literature by [33], QCA has been developed ever since (see, for example, [32] or [34]. Used originally in social sciences like sociology, recently it has also been used in areas related to economics and management, with applications on countries' economic performance [35], export performance [36], economic growth [37], innovation [38] or entrepreneurship [39,40]. Despite this general use of fsQCA, no other studies were found to identify the conditions to evaluate city branding.…”
Section: # Variable and Unit Yearmentioning
confidence: 99%
“…Introduced in the literature by [33], QCA has been developed ever since (see, for example, [32] or [34]. Used originally in social sciences like sociology, recently it has also been used in areas related to economics and management, with applications on countries' economic performance [35], export performance [36], economic growth [37], innovation [38] or entrepreneurship [39,40]. Despite this general use of fsQCA, no other studies were found to identify the conditions to evaluate city branding.…”
Section: # Variable and Unit Yearmentioning
confidence: 99%
“…The main sufficient condition for both outcomes is a good research system. Ferreira and Dionísio (2016) [14] used a crisp-set qualitative comparative analysis of data from European Union countries to establish which conditions could be considered necessary and sufficient to make these countries converge. Based on six different conditions (GDP, secondary education, life expectancy, fertility rate, government consumption, and inflation rate), this study found that the main conditions affecting convergence are the government consumption ratio (lower levels will increase convergence), education levels, and life expectancy (both with a positive influence on convergence).…”
Section: Literature Reviewmentioning
confidence: 99%
“…características sociales y comunicaciones), esboza un mapa plagado de desigualdades socioeconómicas (Mairal, 2008;Bouzarovski & Tirado, 2015;Maynou et al, 2015;Carlsen & Bruggemann, 2021;Vinci, 2021), dando lugar a espacios de alta accesibilidad y otros más aislados. La notable disparidad entre territorios europeos queda de manifiesto en indicadores como el Producto Interior Bruto (PIB), que muestra valores superiores en los países pertenecientes a la Unión Europea (en lo sucesivo, UE) que en los que no lo son -aunque estos últimos ocupen un territorio más extenso- (Ezcurra et al, 2004;Ferreira & Dionísio, 2016). Dentro de los países pertenecientes a la UE también existen desigualdades regionales.…”
Section: Introductionunclassified